2011
DOI: 10.1080/17441692.2011.617381
|View full text |Cite
|
Sign up to set email alerts
|

Moving forward on women's gender-related HIV vulnerability: The good news, the bad news and what to do about it

Abstract: The global response to AIDS has triggered unprecedented attention to gender inequality and the role it plays in shaping the vulnerability of women. Tragically, however, this attention has not yet led to wide-scale transformations in gender roles, or reductions in gender-related risk. This paper reviews both knowledge and action on the impact of gender inequality on women in the context of HIV prevention, and argues that, while much is known, and while effective strategies do exist, impact on a population level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 29 publications
0
33
0
1
Order By: Relevance
“…(14)(15)(16)(17) Differences between the sexual behavior of men and women should be considered in planning prevention policies and control of STDs.…”
Section: Discussionmentioning
confidence: 99%
“…(14)(15)(16)(17) Differences between the sexual behavior of men and women should be considered in planning prevention policies and control of STDs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ashburn et al (2009) have suggested that the World Bank and the Global Fund for HIV, TB and Malaria both developed and implemented gender policies that have helped transform their approaches in the response to HIV, even if these policies have not been implemented programmatically. However, in other contexts integrating gender into global health policy remains elusive (Hawkes and Buse 2013) and HIV policies, while acknowledging the importance of gender inequalities, have not translated this into meaningful policy and programmatic language (Tallis 2000, Greig et al 2008, Gupta et al 2011, Gibbs et al 2012.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, women continue to undertake most care work for people living with HIV and AIDS (Gouws et al 2008, UNAIDS 2012. Gender inequality refers to the socially constructed relationship between men and women, which proscribes certain behaviours and roles within a community (Connell 2009, Gupta et al 2011. Such disparities are linked to power imbalances, which structure inequitable access to resources and are a cause of intimate partner violence, women's inability to negotiate condom use and to take control of their sexual health, increasing women's risk of acquiring HIV (Greig et al 2008, Jewkes andMorrell 2010).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, in many cultures there are men who have sexual intercourse with other men, but would never identify themselves as 'gay', 'homosexual' or most certainly, 'MSM' (Boyce et al 2007, Dowsett 2009). Rao Gupta et al (2011) describe how stereotyped assumptions about women's sexuality and sexual interests have masked much more complex realities, leading to prevention programming that radically misses the mark. Chandler (2011) touches upon how such assumptions have marred the effectiveness of youth-oriented prevention.…”
Section: Introductionmentioning
confidence: 99%